Surface enrichment of iridium on IrCo alloys for boosting hydrogen production. Issue 31 (29th July 2021) - Dang, Ngoc Kim; Umer, Muhammad; Thangavel, Pandiarajan; Sultan, Siraj; Tiwari, Jitendra N.; Lee, Jong Hoon; Kim, Min Gyu; Kim, Kwang S.
Abstract : The enrichment of Ir atoms on the outer surface of IrCo alloy favors hydrogen adsorption in terms of the effectively optimized free energy, which boosts the kinetics and HER performance in acidic solution. Abstract : We report a facile synthesis of an Ir surface-enriched IrCo alloy catalyst and its excellent activity which outperforms commercial Pt/C for the hydrogen evolution reaction (HER) in acidic media showing fast kinetics. The as-synthesized catalyst exhibits low overpotentials of merely 9 mV and 29.3 mV to afford current densities of 10 and 100 mA cm −2, respectively, a turnover frequency of 1.25 s −1, a low Tafel slope of 23.7 mV dec −1, and stability for 100 h at a high current density of 100 mA cm −2 in 0.5 M H2 SO4 electrolyte. Experiments and density functional theory (DFT) calculations indicate that the enrichment of Ir atoms on the outer surface of IrCo alloys is responsible for the effectively optimized free energy of hydrogen adsorption, which boosts the kinetics and HER performance. Our finding provides an insight into the metal surface enrichment on alloy nanoparticles (NPs).